Oxidative stress-induced cell cycle blockage and a protease-independent programmed cell death in microaerophilic Giardia lamblia - Esha Ghosh; Arjun Ghosh; Amar Nath Ghosh; Tomoyoshi Nozaki; Sandipan Ganguly (Dove Medical Press, 2009)
Esha Ghosh1, Arjun Ghosh1, Amar Nath Ghosh2, Tomoyoshi Nozaki3, Sandipan Ganguly11Division of Parasitology; 2Division of Electron Microscopy, National Institute of Cholera and Enteric Diseases, Beliaghata, Kolkata, West Bengal, India; 3Division of Parasitology, National Institute of Infectious Diseases, Tokyo, JapanAbstract: Giardia lamblia is a microaerophilic human gastrointestinal parasite and considered as an early-diverged eukaryote. In vitro oxidative stress generation plays a significant role in cell cycle progression and cell death of this parasite. In the present study hydrogen peroxide, metronidazole, and a modified growth medium without cysteine and ascorbic acid have been chosen as oxidative stress-inducing agents. Cell cycle progression has been found to be regulated by different types of oxidative stresses. Apoptosis is not an established pathway in Giardia, which is devoid of ideal mitochondria, but in the present investigation, apoptosis-like programmed cell death has been found by the experiments like AnnexinV-FITC assay, DNA fragmentation pattern, etc. On the contrary, Caspase-9 assay, which confirms the caspase-mediated apoptotic pathway, has been found to be negative in all the stress conditions. Protease inhibitor assay confirmed that, even in absence of any proteases, programmed cell death does occur in this primitive eukaryote. All these results signify a novel pathway of programmed suicidal death in Giardia lamblia under oxidative stress. This is the first demonstration of protease-independent programmed cell death regulation in Giardia exclusive for its own specialties.Keywords: Giardia lamblia, oxidative stress, reactive oxygen species, programmed cell death, apoptosis, early branching eukaryotes